El libro de dirección como herramienta pedagógica para la formación de Licenciados en Artes Escénicas (2019)
The present work is a qualitative researchexercise, around the books of managementthat are in the documentation centre of theUniversity library Antonio Nariño, Iberianheadquarters. It was considered to make anobservation of the books of direction (beingthese result of a work written to opt for thedegree, in level of undergraduate andpostgraduate) considering, first the quantityof books of direction that there is in thelibrary a Iberian headquarters, then Make aselection by subject and classify them bystructure.